2020
DOI: 10.1007/s12298-019-00733-w
|View full text |Cite|
|
Sign up to set email alerts
|

Callus culture and plantlet regeneration in date palm (Phoneix dactylifera L.): an important horticultural cash crop for arid and semi-arid horticulture

Abstract: Phoneix dactylifera L. commonly called date palm is a highly valuable horticultural cash crop for arid and semi-arid regions. The availability of offshoots and their survival during plantation are major concern. Being dioecious tree, seed propagation in date palm do not produce true-to-type offspring and tissue culture propagation is the only viable option to supply quality-planting propagules. Hereby, we report callus culture and plantlet regeneration in female date palm using in vitro-derived adventitious sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The study showed that 2.0 mg/L CPPU and 0.2 mg/L 2-ip can promote callus induction, and 3.0 mg/LCPPU can promote the growth of embryogenic callus in blueberry leaves ( Figure 1 and Figure 2 ; Table 9 and Table 10 ). In addition, CPPU [ 36 , 37 , 38 ] and 2iP [ 39 , 40 , 41 ] are active and promote bud growth in blueberries. In the present experiment, 1.0 mg/LCPPU and 0.4 mg/L 2-ip promote bud production and growth in blueberry, and the growth state of buds is better ( Figure 3 ; Table 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that 2.0 mg/L CPPU and 0.2 mg/L 2-ip can promote callus induction, and 3.0 mg/LCPPU can promote the growth of embryogenic callus in blueberry leaves ( Figure 1 and Figure 2 ; Table 9 and Table 10 ). In addition, CPPU [ 36 , 37 , 38 ] and 2iP [ 39 , 40 , 41 ] are active and promote bud growth in blueberries. In the present experiment, 1.0 mg/LCPPU and 0.4 mg/L 2-ip promote bud production and growth in blueberry, and the growth state of buds is better ( Figure 3 ; Table 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Auxins are the best PGRs to enhance chances of callus formation [ 29 , 30 ]. Among the different auxins used, picloram and 2,4-D were the auxins that were successfully induced callus from leaf and midrib explants of P. bullata followed by NAA.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro derived callus formation maximum observed in 2,4-D similarely in combination of 2,4-D only shown high callus formation in Jasminum sambac. Similar hormone combination has shown higher activity in Jasminum grandiflorum plant [9,18]. The causes of gastric ulcer are whispered due to stress triggered the addition of hydrochloric acid secretion and/or stasis, and the rate discharge is also an important reason in the ulcer configuration due to the exposure of the stomach's undefended lumen to the accumulating acid [19].…”
Section: Ulcer Scorementioning
confidence: 99%